2021
DOI: 10.1021/acscatal.1c01611
|View full text |Cite
|
Sign up to set email alerts
|

Rigid Postmetallocene Catalysts for Propylene Polymerization: Ligand Design Prevents the Temperature-Dependent Loss of Stereo- and Regioselectivities

Abstract: Energy- and cost-efficient production of polyolefins in solution processes is achieved, inter alia, by conducting polymerizations at high temperatures. Such processes using single-site catalysts (SSCs) based on group 4 complexes are widely used for the production of ethylene copolymers [e.g., linear low-density polyethylene (LLDPE)], but their implementation in the isotactic polypropylene (iPP) segment remains hampered by the challenge of producing high-melting iPP at high temperatures. Known SSCs (mostly meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
(101 reference statements)
0
6
0
2
Order By: Relevance
“…Based on the above results, it is concluded that the binuclear complexes have better thermal stability and lower sensitivity to the n (Al)/ n (Ti) ratio. This may be due to the rigid p -phenyl bridge structure, which provides a more active metal center stable state than the mononuclear complexes at high temperatures . Furthermore, it hinders the progress of β-H elimination and chain transfer reactions, thereby increasing the molecular weight of the produced polymers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above results, it is concluded that the binuclear complexes have better thermal stability and lower sensitivity to the n (Al)/ n (Ti) ratio. This may be due to the rigid p -phenyl bridge structure, which provides a more active metal center stable state than the mononuclear complexes at high temperatures . Furthermore, it hinders the progress of β-H elimination and chain transfer reactions, thereby increasing the molecular weight of the produced polymers.…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to the rigid p-phenyl bridge structure, which provides a more active metal center stable state than the mononuclear complexes at high temperatures. 37 Furthermore, it hinders the progress of β-H elimination and chain transfer reactions, thereby increasing the molecular weight of the produced polymers.…”
Section: Resultsmentioning
confidence: 99%
“…6 The non-obvious coupling of the latter two effects complicates rational tuning. On the other hand, we have recently shown that limiting catalyst flexibility can dramatically increase catalyst performance, 21 even in systems as well studied as ansa -metallocenes. 22,23…”
Section: Introductionmentioning
confidence: 99%
“…[9] Tatsächlich erhielt Ewen eine iPP/aPP-Mischung (Verhältnis 2 : 1) durch Polymerisation von rac/meso Et-(Ind) 2 -TiCl 2 mit Methylaluminoxan (MAO). [9a] Neugierig über die Performance unseres Referenz-Katalysatorsystems rac-I von unserer Gruppe, [4] isolierten wir das Hafnocen meso-I (Schema 1) und untersuchten dessen Polymerisation von Propylen nach in situ Aktivierung. [10] Anstatt aPP lieferte die Polymerisation von meso-I bei 30 Voskoboynikov und Mitarbeiter erzielten für die Anion-induzierte meso-zu-rac Isomerisierung von meso-I zu rac-I eine Ausbeute von 95 %.…”
unclassified
“…[3] Nachdem diese Hafnocene eine schwache Performance bei erhöhten Temperaturen zeigten, untersuchten Voskoboynikov und Mitarbeiter Zirconocene, welche bei Hochtemperaturen eine verbesserte Leistung aufwiesen. [4] Nichtsdestotrotz, alle ansa-Metallocene besitzen einen großen Nachteil: die notwendige und sehr aufwendige Trennung der rac und meso Isomere. Diese benötigt normalerweise mehrere Umkristallisationen, [3b] wohingegen bisher für manche Metallocene noch keine geeigneten Trennungsbedingungen gefunden wurden.…”
unclassified